Spinel structure multi-component composite oxide catalyst and preparation method thereof
By using spinel structure multi-component oxides to support multiple active metal nanoparticles in catalysts, the problems of low and uncontrollable carbon nanotube synthesis yield in the prior art are solved, and high-quality and high-yield carbon is achieved Nanotube synthesis.
Patent Information
- Application Number
- CN202411504111.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
AI Technical Summary
It is difficult to achieve high-quality and high-yield synthetic carbon nanotubes in the prior art, and the preparation method of catalysts has problems such as uncontrollability and low yield.
A spinel structure multi-component oxide catalyst is used to form a catalyst with special ion exchange capability by supporting various active metal nanoparticles such as iron, cobalt, and nickel on base metal oxides such as magnesium and aluminum. The catalyst uses hydrocarbon gas as carbon source at high temperatures by chemical vapor deposition to achieve high-speed synthesis of carbon nanotubes.
The high yield and high-quality growth of carbon nanotubes are achieved, with a growth rate of more than 25 times the weight of the catalyst, and the catalyst has good thermal stability and controllability, which is suitable for large-scale production.
Smart Images

Figure CN119500150A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a spinel structure multi-component composite oxide catalyst, a preparation method thereof, and an application of the catalyst in synthesizing carbon nanotubes with high yield. Background Art
[0002] Carbon nanotubes are seamless nanotubes made of single or multi-layer graphene sheets curled in a certain direction. Both ends are often sealed by hemispherical large fullerene molecules. The diameter is in the nanometer level and the length is in the micrometer level. They usually have a very high aspect ratio. 2 The hybrid and hollow structure give it extraordinary mechanical, thermal and electrical properties, such as low density, outstanding tensile strength and stiffness, excellent thermal and electrical conductivity, high ductility, high chemical stability, etc. Therefore, carbon nanotubes are a high-performance carbon nanomaterial with a wide range of applications, including large-volume applications such as conductive, electromagnetic, high-strength composite materials, supercapacitors, battery electrodes, fuel cell catalysts, transparent conductive films, field emission displays and photovoltaic devices; and limited-volume applications such as scanning probe tips, drug delivery systems and biosensors. The market demand for carbon nanotubes is still growing today. However, due to the complexity of the growth mechanism of carbon nanotubes, the limitations of the production method and the uncontrollability of the production process, the output of commercially produced carbon nanotubes is still generally low and cannot meet the application needs. Therefore, the scale-up research on the high-quality and high-yield synthesis of carbon nanotubes has always been the focus of attention.
[0003] Traditional preparation methods for carbon nanotubes include arc discharge, laser ablation and chemical vapor deposition. Chemical vapor deposition has become the most common technology for preparing carbon nanotubes and is also the method most promising for large-scale production of carbon nanotubes due to its low reaction temperature, mild conditions, simple equipment, large system output, easy continuity, convenient product collection, and stable and reliable production.
[0004] In the chemical vapor deposition growth of carbon nanotubes, catalysts play a key role. Transition metals are the most common catalytically active metals, and there are often more than one transition metal element in the catalyst, and the roles played by different transition metal elements are also very different. Often the second and third transition metals are added as co-catalysts, interacting with the main catalyst transition metal atoms for synergistic catalysis, so as to better disperse metal nanoparticles, maintain the activity of the main catalyst, and increase the density of catalytic active sites. In addition to active metals, the strong interaction between the substrate and the metal in the catalyst and the uniform dispersion of active species in the substrate are also key factors in fully exerting the catalytic performance of the catalyst. In order to improve the interaction between the substrate and the active metal, some researchers have proposed to mix the active metal in the catalyst with the substrate element in advance, so that the active metal and the substrate element can form a catalyst precursor together through processes such as crystallization and precipitation. This ensures that the catalyst has the advantages of high transition metal content, uniform distribution of high active sites, small grains, inhibition of sintering, and good thermal stability. After the catalyst precursor is dried, calcined and other processes, a composite metal oxide composed of oxides of different structures will be obtained, which can effectively regulate the interaction between different active metals and the substrate, highly disperse the active metal nanoparticles, maximize the potential for growing carbon nanotubes, and increase the catalyst growth density. Therefore, to achieve high-rate synthesis of carbon nanotubes, it is necessary to regulate the catalyst composition and change the catalyst preparation method to maximize the role of active metals and substrates, so that as many active metal particles as possible have the ability to grow. Therefore, preparing a highly dispersed multi-supported catalyst is of great significance for achieving large-scale preparation of carbon nanotubes.
[0005] CN109926050 discloses a method for preparing a carbon nanotube metal symbiotic material, comprising the following steps: (1) adding deionized water after mixing a metal source and a carrier, soaking for 2-4 hours under ultrasonic treatment, filtering, washing the obtained filter residue with deionized water, drying, and calcining to obtain a metal-based catalyst; or directly calcining the metal source to obtain a metal-based catalyst; (2) placing the metal-based catalyst in a reactor, first introducing an inert gas to replace it, then introducing a reducing gas, heating to 500-800°C, stopping the introduction of the reducing gas, and then introducing a carbon source, reacting for 1-5 hours, introducing an inert gas again, and cooling the temperature to room temperature in the inert gas atmosphere to obtain a carbon nanotube metal symbiotic material. The carbon nanotubes obtained by the preparation method grow on metal particles, which can ensure the uniformity of the diameter of the carbon nanotubes and the metal particles. The diameter of the material finally prepared is about 500nm, and has good catalytic performance.
[0006] CN104812484A discloses a method for preparing a supported catalyst and a carbon nanotube assembly. The catalyst is a quaternary supported catalyst prepared by sequentially adding polycarboxylic acid and precursors of the first and second catalytic components (such as Co and Fe) to precursors of the first and second active components (such as Mo and V) to obtain a transparent metal solution, which is then impregnated on an alumina-based granular carrier and subsequently dried and calcined. The carbon nanotube assembly synthesized in the invention can form a specific morphology, i.e., carbon nanotubes grown in bundles on the supported catalyst. The bulk density of the obtained catalyst is 0.8 to 1.5 g / cm 3 The average particle size of the product bundled carbon nanotubes is 100 to 800 μm, and the bulk density is 80 to 250 kg / m 3 , spherical or potato-shaped, and has a wide range of possible applications.
[0007] CN114572966A discloses a method for synthesizing carbon nanotubes using a layered iron-cobalt-aluminum catalyst. The key steps include preparing a layered catalyst by treating expanded vermiculite with a metal salt solution, then reducing the catalyst and using it to catalyze propylene cracking in a fluidized bed reactor to produce carbon nanotubes. The resulting carbon nanotube product contains a low content of ferromagnetic metal impurities and good electrical conductivity, and is suitable for use in lithium-ion batteries for new energy vehicles. Summary of the invention
[0008] The present invention uses two or three mixed salts of divalent and trivalent metal salts such as magnesium salt, aluminum salt, zinc salt, manganese salt, iron salt, cobalt salt, titanium salt, chromium salt, nickel salt, etc. as a composite substrate precursor, and loads at least two to five different transition metal nanoparticles of iron, cobalt, nickel, ruthenium, molybdenum, manganese, platinum, palladium, and chromium on the composite substrate precursor as catalytic active components to prepare a spinel phase structure multi-component composite metal oxide catalyst. Since the crystal structure of the composite metal oxide substrate has a special ion exchange capacity, in some cases, the various metal ions constituting the substrate can also be replaced in the process of growing carbon nanotubes to play a catalytic role, so the catalyst can change the surface properties and composite structure through position exchange, so that the base metal and the active metal synergistic catalysis, and is a multi-functional combination of efficient catalysts. For example, composite manganese oxide and alumina substrates containing manganese-aluminum spinel structures are loaded with Fe and Mo, and composite alumina, iron oxide and alumina substrates containing magnesium-iron-aluminum spinel structures are loaded with Co, Ni, etc. Under the optimal reaction conditions, high-rate synthesis of carbon nanotubes is achieved by chemical vapor deposition, mainly using hydrocarbon gases such as methane, ethylene or propylene as carbon sources. The growth rate of carbon nanotube powder can reach more than 25 times the weight of the catalyst.
[0009] The present invention uses hydrocarbon gas as a carbon source, adopts a substrate containing a composite oxide with a spinel phase structure, and disperses multiple active transition metals to form a supported catalyst to achieve high-rate synthesis of carbon nanotubes. When preparing the catalyst, 2-5 different transition metal oxides of iron, cobalt, nickel, ruthenium, molybdenum, manganese, platinum, palladium, and chromium are loaded on the composite metal oxide containing the spinel phase structure as active components. During the reaction process, hydrocarbon gases such as C1-C6 alkanes and low-carbon olefins are used as carbon sources, inert gases such as nitrogen and argon are used as protective gases, and gases such as hydrogen are used as reducing gases. Chemical vapor deposition is used under normal pressure to achieve high-yield synthesis of carbon nanotubes at a reaction temperature set at 600-900°C.
[0010] The present invention mainly uses a multi-transition metal-supported catalyst dispersed in a composite metal oxide containing a spinel structure to achieve high-rate synthesis of carbon nanotubes, using at least two and at most five different transition metal nanoparticles (such as iron, cobalt, nickel, ruthenium, molybdenum, manganese, platinum, palladium, chromium, etc.) dispersed on a composite substrate as catalysts, and adopts chemical vapor deposition method to catalyze the cracking of hydrocarbon gas to achieve high-rate synthesis of carbon nanotubes.
[0011] A spinel structure multi-component composite oxide catalyst comprises an active metal and a base metal composite oxide, wherein the active metal is 2-5 of iron, cobalt, nickel, ruthenium, molybdenum, manganese, platinum, palladium and chromium; the base metal is a mixture of two or three of magnesium, aluminum, zinc, manganese, iron, cobalt, titanium, chromium and nickel; the particle size of the catalyst particles is 2-50 nanometers, more preferably 2-20 nanometers.
[0012] The trivalent metal in the multi-component composite oxide catalyst should account for 0.1-0.4 of the total molar number of metals in the catalyst.
[0013] The molar ratio of the active metal to the base metal is 0.01-0.1, more preferably 0.02-0.1.
[0014] A method for preparing a spinel structure multi-component composite oxide catalyst comprises the following steps: (1) Mixing the active metal precursor and the base metal precursor and dissolving them in a solvent, adding additives and adjusting the pH to 7-10; (2) Stir vigorously to mix all components evenly and allow them to age and crystallize; (3) re-adjusting the pH of the mixture obtained in step (2), and thoroughly drying the catalyst precursor by drying or freeze-drying; (4) Calcining the dried precursor to obtain a multi-component composite oxide catalyst containing a spinel structure.
[0015] The active metal in step (1) is three of iron, cobalt, nickel, ruthenium, molybdenum, manganese, platinum, palladium and chromium; the precursor of the active metal is one or more of oxides, hydroxides, chlorides, nitrates, sulfates, silicates and organic acid salt compounds containing the active metal; the precursor of the base metal is a mixed metal salt of two or three of the nitrates of magnesium, aluminum, zinc, manganese, iron, cobalt, titanium, chromium and nickel; the solvent used in the solution is water or one of low-carbon alcohols, and the low-carbon alcohol is a monohydric or polyhydric alcohol of C1-C5, preferably one of methanol, ethanol, propanol and n-butanol.
[0016] The additive in step (1) is one or a mixture of two of sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, and urea, and the concentration of the additive is 0.15-4 mol / L.
[0017] The aging time in step (2) must meet the requirements of sufficient crystallization of the composite oxide structure and high dispersion of the octahedral and tetrahedral positions in the spinel phase substituted by some active metals. The aging crystallization time is 10-45h, preferably 12-38h.
[0018] The pH value in step (3) is 7-9, and deionized water or low-carbon alcohol can be used in the adjustment process.
[0019] The drying temperature in step (3) is 80°C-140°C, and the time is 3-30 hours; the freeze-drying temperature is -20°C to -50°C, the pressure is 0.1-300Pa, and the duration is 10-45 hours.
[0020] The calcination temperature in step (4) is 500-1000°C, more preferably 700-1000°C, most preferably 800-1000°C, and the calcination time is preferably 3h-6h.
[0021] A method for preparing carbon nanotubes using the catalyst, wherein the growth temperature of the carbon nanotubes is controlled at 600°C-900°C, and in the presence of the catalyst described in the present application, a mixed gas of a hydrocarbon carbon source, hydrogen and an inert gas is introduced during a chemical vapor deposition process, wherein the molar ratio of the hydrocarbon carbon source, hydrogen and the inert gas is 5-10:1-3:10-20; more preferably 6-8:1-2:13-16; the reaction time is 1-5h, more preferably 0.5-3h, the hydrocarbon carbon source is one or more of C1-C6 alkanes and alkenes; and the inert gas is one or more of nitrogen, helium and argon.
[0022] Beneficial technical effects of the present invention: (1) The present invention prepares a catalyst by loading a combination of multiple active metals on a composite metal oxide containing a spinel phase structure. First, the active metal and the substrate precursor are evenly mixed, and through processes such as aging and crystallization, the active metal dispersion process and the substrate metal oxide crystal structure reorganization process are carried out simultaneously. Part of the active metal directly participates in the composition of the composite metal oxide, so that it can be dispersed in the substrate at the atomic level. The formation of the spinel phase structure further prevents the formation of active metal clusters in the composite substrate, and a catalyst with a larger specific surface area, higher catalytic efficiency, and higher growth density can be obtained. At the same time, the composite oxide substrate has a strong interaction with the active metal, good thermal stability, and outstanding controllability. The directional growth, size control, and morphology control of carbon nanotubes can be achieved by adjusting the composition, morphology, and structure of the catalyst, thereby achieving precise control of growth.
[0023] (2) The present invention uses a multi-active metal catalyst. Each single metal catalyst system has its own characteristics and advantages, but it is difficult to obtain high-yield and structurally controllable carbon nanotubes in the same system. The multi-metal catalyst system may combine the characteristics and advantages of different metals to obtain a synergistic catalytic effect, which can effectively regulate the binding energy between metal and carbon, carbon solubility and diffusion rate, and improve the high-temperature structural stability of the catalyst. It has obvious advantages in efficient and controllable growth, and has greater room for activity and structural selectivity in growing carbon nanotubes.
[0024] (3) The growth of carbon nanotubes in the present invention is carried out under normal pressure, the preparation process is relatively simple, the production cost is relatively low, and the yield of grown carbon nanotubes is high and the catalytic efficiency of the catalyst is high, which is conducive to the large-scale production of commercial carbon nanotubes.
[0025] (3) In the present invention, hydrocarbon gases such as C1-C6 alkanes and olefins are used as carbon sources, which are cracked at high temperatures to obtain carbon atoms and generate hydrogen, which can reduce metal catalysts, ensure high activity of transition metal nanoparticles, and etch the coated amorphous carbon, which is conducive to the production of high-quality carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the reaction device used in the present invention, wherein 1 is a heating zone, 2 is a quartz boat, and 3 is a catalyst; Figure 2 is a scanning electron microscope image of a carbon nanotube product synthesized by the catalyst prepared by the present invention without calcination; Figure 3 is a scanning electron microscope image of the carbon nanotube product synthesized in Example 1; Figure 4 is a scanning electron microscope image of the carbon nanotube product synthesized in Example 6. DETAILED DESCRIPTION
[0027] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific implementation methods described below, and similar technologies and methods should be considered to be within the scope of protection of the present invention. In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.
[0028] The present invention is further described in detail below with specific implementation modes.
[0029] Example 1 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding sulfates of iron, cobalt and nickel metal elements in an equal molar ratio to deionized water, adding a mixed salt of aluminum nitrate and zinc nitrate in a molar ratio of active metal to substrate of 0.05, wherein the aluminum nitrate accounts for 0.19 of the total molar number of aluminum nitrate and zinc nitrate; adjusting the pH of the solution to 10 with sodium hydroxide having a concentration of 2 mol / L; aging the catalyst precursor solution for 26 hours; re-adjusting the pH to 8 with deionized water; and then adding the catalyst to a freeze dryer, maintaining the sample temperature at -35°C; and continuously drying the sample at a pressure of 10 Pa for 36 hours to obtain a solid catalyst; and grinding the sample and calcining the sample at 800°C-900°C for 4 hours in a muffle furnace to obtain a highly dispersed iron-cobalt-nickel trimetallic supported catalyst.
[0030] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of ethylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 26.25 times the original mass of the catalyst.
[0031] Example 2 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding hydrated nitrates of cobalt and nickel metal elements in a molar ratio of 1:0.5 to deionized water, and adding a mixed salt of magnesium sulfate, zinc sulfate and aluminum sulfate in a molar ratio of active metal to substrate of 0.1, wherein the aluminum sulfate accounts for 0.27 of the total molar number of magnesium sulfate, zinc sulfate and aluminum sulfate metals; adjusting the pH of the solution to 9 with urea having a concentration of 3 mol / L; aging the catalyst precursor for 12 hours; re-adjusting the pH to 7 with deionized water and ethanol in turn; and then adding the catalyst into a freeze dryer, maintaining the sample temperature at -50°C, and continuously drying the sample at a pressure of 100 Pa for 28 hours to obtain a solid catalyst; and grinding the sample to obtain a highly dispersed cobalt-nickel bimetallic supported catalyst.
[0032] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of propylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 23.65 times the original mass of the catalyst.
[0033] Example 3 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding a hydrated nitrate of cobalt and chlorides of molybdenum and nickel metal elements in a ratio of 1:0.5:0.3 to deionized water, and adding a mixed salt of zinc nitrate and aluminum nitrate in a molar ratio of active metal to substrate of 0.01, wherein the aluminum nitrate accounts for 0.16 of the total molar number of zinc nitrate and aluminum nitrate metals; adjusting the pH of the solution to 10 with a mixed solution of sodium bicarbonate and sodium hydroxide at a concentration of 3 mol / L; aging the catalyst precursor for 18 hours, readjusting the pH to 8 by washing with ethanol, and then drying at 110°C for 12 hours to obtain a solid catalyst; and grinding and calcining the solid catalyst at 600°C-800°C for 6 hours in a muffle furnace to obtain a highly dispersed cobalt, molybdenum and nickel trimetallic supported catalyst.
[0034] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of methane, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 22.71 times the original mass of the catalyst.
[0035] Example 4 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding chlorides of cobalt, chromium and copper metal elements in a ratio of 1:0.02:0.02 to deionized water, and adding a mixed salt of zinc nitrate, ferric nitrate and aluminum nitrate in a molar ratio of active metal to substrate material of 0.02, wherein the aluminum nitrate and ferric nitrate account for 0.23 and 0.15 of the total molar number of zinc nitrate, aluminum nitrate and ferric nitrate, respectively; adjusting the solution pH to 9 with sodium hydroxide having a concentration of 1.5 mol / L; aging the catalyst precursor for 24 hours; re-adjusting the pH to 9 by washing with deionized water; and then placing the catalyst in a freeze dryer, maintaining the sample temperature at -20°C, and continuously drying the sample at a pressure of 200 Pa for 40 hours to obtain a solid catalyst; and calcining the sample at 900°C-1000°C for 3 hours in a muffle furnace after grinding to obtain a highly dispersed cobalt, chromium and copper tri-metal supported catalyst.
[0036] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of ethylene, hydrogen and argon is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 24.73 times the original mass of the catalyst.
[0037] Example 5 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding chlorides of iron and chromium metal elements in a molar ratio of 1:0.2 to deionized water, and adding a mixed salt of manganese nitrate, magnesium nitrate and aluminum sulfate in a molar ratio of active metal to substrate of 0.03, wherein the aluminum nitrate accounts for 0.37 of the total molar number of manganese nitrate, magnesium nitrate and aluminum nitrate; adjusting the solution pH to 10 with sodium bicarbonate having a concentration of 2 mol / L; aging the catalyst precursor for 30 hours; re-adjusting the pH to 8 by washing with deionized water; and then drying at 100°C-200°C for 24 hours to obtain a solid catalyst; and grinding and calcining the catalyst at 1000°C for 3 hours in a muffle furnace to obtain a highly dispersed iron-chromium bimetallic supported catalyst.
[0038] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of propylene, hydrogen and argon is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 23.54 times the original mass of the catalyst.
[0039] Example 6 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding hydrated nitrates of iron and cobalt in a molar ratio of 1:0.2 to deionized water, and adding magnesium nitrate, zinc nitrate and aluminum nitrate in a molar ratio of active metal to substrate of 0.1, wherein the aluminum nitrate accounts for 0.3 of the total molar number of magnesium nitrate, zinc nitrate and aluminum nitrate; adjusting the pH of the solution to 10 with sodium bicarbonate having a concentration of 1.5 mol / L; aging the catalyst precursor for 20 hours; re-adjusting the pH to 8 by washing with deionized water; maintaining the sample temperature at -40°C; and continuously drying at 100 Pa for 35 hours to obtain a solid catalyst; and grinding to obtain a highly dispersed iron-cobalt bimetallic supported catalyst.
[0040] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of ethylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 25.89 times the original mass of the catalyst.
[0041] Example 7 A multi-metal catalyst dispersed in a spinel phase composite metal oxide is prepared to achieve high-yield synthesis of carbon nanotubes. The method comprises: adding hydrated chlorides of cobalt, manganese and ruthenium in a molar ratio of 1:0.5:0.02 to deionized water, adding a mixed salt of magnesium sulfate and aluminum sulfate in a molar ratio of active metal to substrate of 0.1, wherein the aluminum sulfate accounts for 0.19 of the total molar number of magnesium sulfate and aluminum sulfate metals, adjusting the pH of the solution to 10 with urea having a concentration of 3 mol / L, aging the catalyst precursor for 32 hours, re-adjusting the pH to 7 by washing with deionized water, maintaining the sample temperature at -47°C, and continuously drying at 100 Pa for 36 hours to obtain a solid catalyst, and calcining the solid catalyst at 800°C-1000°C for 5 hours in a muffle furnace after grinding to obtain a highly dispersed cobalt-manganese-ruthenium trimetallic supported catalyst.
[0042] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of propylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 24.13 times the original mass of the catalyst.
[0043] Comparative Example 1 0.003 mol of ferric nitrate was added to deionized water, and a mixed salt of zinc nitrate and aluminum nitrate was added at a molar ratio of 0.05 between the active metal and the substrate, with aluminum nitrate accounting for 0.19 of the total molar number of zinc nitrate and aluminum nitrate metals. The pH of the solution was adjusted to 10 with a mixed alkali solution of sodium hydroxide and sodium carbonate at a concentration of 2 mol / L. The catalyst precursor solution was aged for 26 hours, washed with deionized water to readjust the pH to 8, and then added to a freeze dryer. The sample temperature was maintained at -35°C, and dried continuously at a pressure of 10 Pa for 36 hours to obtain a solid catalyst. After grinding, the solid catalyst was calcined at 800°C-900°C in a muffle furnace for 4 hours to obtain a highly dispersed iron metal supported catalyst.
[0044] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of ethylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 12.37 times the original mass of the catalyst.
[0045] Comparative Example 2 0.003 mol of cobalt nitrate was added to deionized water, and a mixed salt of magnesium nitrate and aluminum nitrate was added at a molar ratio of 0.02 between active metal and substrate, with aluminum nitrate accounting for 0.26 of the total molar number of magnesium nitrate and aluminum nitrate. The pH of the solution was adjusted to 10 with 3 mol / L urea. The catalyst precursor solution was aged for 24 hours, washed with deionized water to readjust the pH to 7, and then added to a freeze dryer. The sample temperature was maintained at -50°C, and dried continuously at a pressure of 10 Pa for 36 hours to obtain a solid catalyst. After grinding, the solid catalyst was calcined at 800°C-900°C in a muffle furnace for 4 hours to obtain a highly dispersed cobalt metal supported catalyst.
[0046] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of ethylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 9.86 times the original mass of the catalyst.
[0047] Comparative Example 3 0.003 mol of nickel nitrate was added to deionized water, and a mixed salt of magnesium nitrate and aluminum nitrate was added at a molar ratio of 0.02 between active metal and substrate, with aluminum nitrate accounting for 0.3 of the total molar number of magnesium nitrate and aluminum nitrate metals. The pH of the solution was adjusted to 9 with 2 mol / L sodium hydroxide. After vigorous stirring, the catalyst precursor solution was aged for 24 hours, washed with deionized water to readjust the pH to 7, and then added to a freeze dryer, followed by continuous drying at 110°C for 12 hours to obtain a solid catalyst. After grinding, the solid catalyst was calcined in a muffle furnace at 950°C-1000°C for 4 hours to obtain a highly dispersed cobalt metal supported catalyst.
[0048] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of ethylene, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 9.86 times the original mass of the catalyst.
[0049] Comparative Example 4 A non-hydrocarbon carbon source gas is used for growth, hydrated nitrates of iron and cobalt metal elements are added to deionized water at a molar ratio of 1:1, and a mixed salt of zinc sulfate and aluminum sulfate is added at a molar ratio of active metal to substrate of 0.05, with aluminum nitrate accounting for 0.27 of the total molar number of zinc nitrate and aluminum nitrate. The pH of the solution is adjusted to 9 with 3 mol / L sodium hydroxide, the catalyst precursor is aged for 20 hours, the pH is readjusted to 8 with deionized water and ethanol washing, and then dried at 100°C for 24 hours to obtain a solid catalyst, which is ground to obtain a highly dispersed iron-cobalt bimetallic supported catalyst.
[0050] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of carbon monoxide, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 15.13 times the original mass of the catalyst.
[0051] Comparative Example 5 A non-hydrocarbon carbon source gas is used for growth, hydrated nitrates of iron and cobalt metal elements are added to deionized water at a molar ratio of 1:1, and a mixed salt of zinc sulfate and aluminum sulfate is added at a molar ratio of active metal to substrate of 0.05, the pH of the solution is adjusted to 9 with 3 mol / L sodium hydroxide, the catalyst precursor is aged for 20 hours, the pH is readjusted to 8 with deionized water and ethanol washing, and then dried at 100°C for 24 hours to obtain a solid catalyst, which is ground to obtain a highly dispersed iron-cobalt bimetallic supported catalyst.
[0052] When the catalyst is used, the above catalyst is placed in a horizontal furnace, the growth temperature is controlled at 600℃-900℃, and a mixed gas of carbon dioxide, hydrogen and nitrogen is introduced during the chemical vapor deposition process. The growth rate of the carbon nanotube powder can reach 13.52 times the original mass of the catalyst.
Claims
1. A spinel structure multi-component composite oxide catalyst, comprising an active metal and a base metal, wherein the active metal is 2-5 of iron, cobalt, nickel, ruthenium, molybdenum, manganese, platinum, palladium, and chromium; the base metal is a mixture of two or three of magnesium, aluminum, zinc, manganese, iron, cobalt, titanium, chromium, and nickel; the particle size of the catalyst is 2-50 nanometers, more preferably 2-20 nanometers.
2. The catalyst according to claim 1, characterized in that The trivalent metal in the precursor mixed salt of the composite substrate should account for 0.1-0.4 of the total molar number of metals in the catalyst.
3. The catalyst according to claim 1, characterized in that The molar ratio of the active metal to the base metal is 0.01-0.1, more preferably 0.02-0.
1.
4. A method for preparing a catalyst as claimed in any one of claims 1 to 3, comprising the following steps: (1) The active metal precursor and the base metal precursor are mixed and dissolved in a solvent, and an additive is added to adjust the pH to 7-10; (2) Stir vigorously to mix all components evenly and allow them to age and crystallize; (3) re-adjusting the pH of the mixture obtained in step (2), and thoroughly drying the catalyst precursor by drying or freeze-drying; (4) Calcining the dried precursor to obtain a composite metal oxide containing spinel oxides, thereby obtaining a highly dispersed multi-supported catalyst.
5. The method according to claim 4, characterized in that The active metal in step (1) is at least two and at most five of iron, cobalt, nickel, ruthenium, molybdenum, manganese, palladium and chromium, and more preferably three of iron, cobalt, nickel, ruthenium, molybdenum, manganese, palladium and chromium; the precursor of the active metal is one or more of oxides, hydroxides, chlorides, nitrates, sulfates, silicates and organic acid salt compounds containing the active metal; the base metal precursor is a mixed salt of two or three of the nitrates of metals such as magnesium, aluminum, zinc, manganese, iron, cobalt, titanium, chromium and nickel; the solvent used in the solution is water or one of low-carbon alcohols, and the low-carbon alcohol is a monohydric or polyhydric alcohol of C1-C5, and preferably one of methanol, ethanol, propanol and n-butanol.
6. The method according to claim 4, characterized in that The additive in step (1) is one or a mixture of two of sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, and urea, and the concentration of the additive is 0.15-4 mol / L.
7. The method according to claim 4, characterized in that The aging time in step (2) must meet the requirements of sufficient crystallization of the composite metal oxide structure and high dispersion of the octahedral and tetrahedral positions in the spinel phase substituted by some active metals. The aging crystallization time is 10-45h, preferably 12-38h.
8. The method according to claim 4, characterized in that In step (3), the pH value is 7-9, and deionized water or low-carbon alcohol can be used in the adjustment process; The drying temperature in step (3) is 80°C-140°C, and the time is 3-30 hours; the freeze-drying temperature is -20°C to -50°C, the pressure is 0.1-300Pa, and the duration is 10-45 hours.
9. The method according to claim 4, characterized in that The calcination temperature in step (4) is 500-1000°C, more preferably 700-1000°C, most preferably 800-1000°C, and the calcination time is preferably 3h-6h.
10. A method for preparing carbon nanotubes, wherein the growth temperature of the carbon nanotubes is controlled at 600°C-900°C, and in the presence of the catalyst as described in any one of claims 1-4, a mixed gas of a hydrocarbon carbon source, hydrogen and an inert gas is introduced during the chemical vapor deposition process, wherein the molar ratio of the hydrocarbon carbon source, hydrogen and the inert gas is 5-10:1-3:10-20; more preferably 6-8:1-2:13-16; the reaction time is 1-5h, more preferably 0.5-3h; the hydrocarbon carbon source is one or more of C1-C6 alkanes and alkenes; the inert gas is one or more of nitrogen, helium and argon.
Citation Information
Patent Citations
Supported catalyst, carbon nanotube assembly, and preparation method therefor
CN104812484A
Cited By
Cobalt-iron double-active-site synergistic catalyst, preparation method thereof and application of cobalt-iron double-active-site synergistic catalyst in carbonate pyrolysis CO2 coupling ethane oxidative dehydrogenation
CN119926407A